2020
DOI: 10.3126/jngmc.v18i1.35211
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Surgical Treatment of Rockwood Type III Acromioclavicular Joint Dislocation Using Clavicle Hook Plate and Tension Band Wiring: A Comparative Study to Evaluate the Functional and Surgical Outcome

Abstract: Introduction: Acromioclavicular joint dislocation Type III is still controversial for its management, despite of numerous trials and reviews. Aims: To compare and evaluate the functional and surgical outcome of Rockwood Type III acromioclavicular joint dislocation treated surgically with clavicular Hook plate and Tension Band wiring with K-wires. Methods: In a prospective hospital based interventional study comprising of total 22 patients with a mean age of 31.36 ± 7.53 years who presented with Rockwood Type I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The clavicular hook plate xation is a convenient and commonly used surgical technique [15], with its supporters suggested that its non-rigid xation could allow the plate to be left in situ for a long term[16], thus providing su cient healing time for the AC and CC ligaments and ensuring the early active functional exercise of the shoulder [17]. Shrestha et al [4] suggested that patients treated with CHP could attain a very better functional and surgical outcomes than K-wire xation. Because of super cial softtissue mantle around the distal clavicle and the AC joint, wound healing issues might be more common after CHP xation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clavicular hook plate xation is a convenient and commonly used surgical technique [15], with its supporters suggested that its non-rigid xation could allow the plate to be left in situ for a long term[16], thus providing su cient healing time for the AC and CC ligaments and ensuring the early active functional exercise of the shoulder [17]. Shrestha et al [4] suggested that patients treated with CHP could attain a very better functional and surgical outcomes than K-wire xation. Because of super cial softtissue mantle around the distal clavicle and the AC joint, wound healing issues might be more common after CHP xation.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of acromioclavicular joint (ACJ) dislocation has increased signi cantly partly due to the increasing rate of tra c accidents and sports injuries, with a direct or an indirect trauma on the upper extremity [1] [2]. Patients with acute ACJ dislocation typically manifested pain, swelling, deformity and signi cant limited range of motion (ROM) of the shoulder [3] [4]. As non-operative treatment might result in moderate rate of persistent pain, instability, and limited mobility [5][6], surgical procedure is recommended especially for high-grade ACJ dislocations classi ed as Rockwood type III and higher, indicating the completely torn acromioclavicular (AC) and coracoclavicular (CC) ligaments [7].…”
Section: Introductionmentioning
confidence: 99%